2021
DOI: 10.3390/cells10092485
|View full text |Cite
|
Sign up to set email alerts
|

The Presence and Potential Role of ALDH1A2 in the Glioblastoma Microenvironment

Abstract: Glioblastoma (GBM) is the most aggressive malignant glioma. Therapeutic targeting of GBM is made more difficult due to its heterogeneity, resistance to treatment, and diffuse infiltration into the brain parenchyma. Better understanding of the tumor microenvironment should aid in finding more effective management of GBM. GBM-associated macrophages (GAM) comprise up to 30% of the GBM microenvironment. Therefore, exploration of GAM activity/function and their specific markers are important for developing new ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Among the 19 members of the aldehyde dehydrogenase super family, aldehyde dehydrogenase 1 family member A2 (ALDH1A2, also known as RALDH2) is one of the most widely distributed members in human tissues [45]. It is reported that ALDH1A2 increases in the hippocampus of senescent female mice [46].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 19 members of the aldehyde dehydrogenase super family, aldehyde dehydrogenase 1 family member A2 (ALDH1A2, also known as RALDH2) is one of the most widely distributed members in human tissues [45]. It is reported that ALDH1A2 increases in the hippocampus of senescent female mice [46].…”
Section: Discussionmentioning
confidence: 99%
“…ZEA (7 μg/mL and 8 μg/mL) can promote ROS production and induce oxidative stress by damaging antioxidant enzyme activity in porcine IPEC-J2 cells [ 6 ]. ALDH1A2, a member of the aldehyde dehydrogenase (ALDH) superfamily, catalyzes the synthesis of retinoic acid (RA), which played a role in cell differentiation, growth and adaptive immune responses [ 58 ]. A study showed that up-regulated ALDH1A2 suppressed ovarian cancer cell proliferation via activation of transcription 3 (STAT3) [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in serum CCL2 and IL-10 titers in these patients further consolidates the above observation. Retinaldehyde dehydrogenase-2 (ALDH1A2) is highly expressed in M2 GAMs in patients with recurrent GBM, whose expression increases with tumor recurrence at the gene and protein level [ 6 ]. ALDH1A2 is enzymatically broken down into retinoic acid (RA), that amplifies the production of MMP 2 and 9 in macrophages, facilitating the progression to more invasive phenotypes of GBM.…”
Section: Laboratory Evidence and The Microglia/macrophages Tmementioning
confidence: 99%
“…In cases of recurrence, a progression-free survival (PFS) of 10 months is usually expected, with an OS of about 22 months even after a second surgery [ 4 , 5 ]. The Cancer Genome Atlas (TCGA) network has classified GBM into four distinct molecular subtypes: classical, mesenchymal, pro-neural, and neural, based on a comprehensive assessment of genetic alterations and expression [ 6 ]. The current standard of care involves maximally safe resection of the tumor followed by radiotherapy and chemotherapy using temozolomide (TMZ).…”
Section: Introductionmentioning
confidence: 99%